A novel sound-blocking structure based on the muffler principle for rib-sparing transcostal high-intensity focused ultrasound treatment. (August 2015) - Chao, Yu-Tin; Hsu, Che-Jung; Yu, Ya-Lin; Yen, Jia-Yush; Ho, Ming-Chih; Chen, Yung-Yaw; Chang, Hung-Cheng; Lian, Feng-Li
Abstract The main challenge in transcostal high-intensity focused ultrasound therapy is minimising heat deposition in the ribs while ensuring that a sufficient dose is delivered to the target region. Current approaches rely on expensive multichannel phased-array systems to turn the individual transducer on and off according to either geometrical arrangements or complicated wave calculations. To protect the ribs from heating, the ultrasound energy must not only not reach the ribs, but must also not accumulate in front of the ribs. The research in this paper proposes a different approach, of attaching a sound-blocking structure in front of the rib cage with similar effects to those of an engine exhaust muffler. The sound-blocking structure is based on the muffler principle to prevent ultrasound energy from reaching the ribs and reduce the amount of energy reflected back to the applicator. Finite element simulations with a 0.5-MHz transducer of the overall sound fields and temperature distribution showed that the ultrasound pressure and energy level would decrease behind the novel sound-blocking structures, thereby resulting in a lower temperature at the ribs than at the tumour. Without the protecting structure, the rib temperature reached 104.19 °C whereas with the structure it reached only 37.86 °C. An experimental set-up using porcine ribs with a phantom was also developed to validate the concept, which showed that the rib temperature reached 73 °C without protection within 1 min of ablation time whereas it reached 36.5 °C with the device. The tumour region in the tests reached 51 °C and 49 °C with and without protection, respectively.